Synthesizing Realistic Human Dance Motions Conditioned by Musical Data using Graph Convolutional Networks - Ferreira, João P. M.; Martins, Renato; Nascimento, Erickson R. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC); 2021: Anais do XXXIV Concurso de Teses e DissertaçõesDO - 10.5753/ctd.2021.15762, 2021)
Learning to move naturally from music, i.e., to dance, is one of the most complex motions humans often perform effortlessly. Existing techniques of automatic dance generation with classical CNN and RNN models undergo training and variability issues due to the non-Euclidean geometry of the motion manifold. We design a novel method based on GCNs to tackle the problem of automatic dance generation from audio. Our method uses an adversarial learning scheme conditioned on the input music audios to create natural motions. The results demonstrate that the proposed GCN model outperforms the state-of-the-art in different experiments. Visual results of the motion generation and explanation can be visualized through the link: http://youtu.be/fGDK6UkKzvA